2013
DOI: 10.14233/ajchem.2013.15114
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of HPLC-ELSD Method for Determination of Swainsonine in Chinese Locoweeds

Abstract: An HPLC method has been optimized and validated for determining swainsonine, a potent glucosidase inhibitor present in locoweeds (any of several plants of the genera Oxytropis and Astragalus in the pea family, which can cause severe poisoning when eaten by livecstock.) of China with isopropanol as a weak eluent. Swainsonine was separated from an extract of locoweeds on hydrophilic interaction chromatography column, using isopropanol-2 mM ammonium acetate (52:48, v/v) as mobile phase at a flow rate of 0.4 mL/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…There are several reported methods of analysis for swainsonine that include TLC, HPLC, and MS methods for the direct analysis of the free base alkaloid as well as gas chromatography methods for the analysis of the trimethylsilyl ether or the triacetyl derivatives of swainsonine. In addition to the occurrence of the free base swainsonine, swainsonine N -oxide, 2 (Figure ), has been reported to occur in several locoweed plants based on isolation and a qualitative TLC method. ,, Qualitative TLC estimates suggested that some locoweeds had similar concentrations of swainsonine and its N -oxide, whereas the N -oxide was not detected by gas chromatography in several Swainsona species tested . Additionally, it has been shown that swainsonine N -oxide was as effective as swainsonine in inhibiting α-mannosidase .…”
Section: Introductionmentioning
confidence: 99%
“…There are several reported methods of analysis for swainsonine that include TLC, HPLC, and MS methods for the direct analysis of the free base alkaloid as well as gas chromatography methods for the analysis of the trimethylsilyl ether or the triacetyl derivatives of swainsonine. In addition to the occurrence of the free base swainsonine, swainsonine N -oxide, 2 (Figure ), has been reported to occur in several locoweed plants based on isolation and a qualitative TLC method. ,, Qualitative TLC estimates suggested that some locoweeds had similar concentrations of swainsonine and its N -oxide, whereas the N -oxide was not detected by gas chromatography in several Swainsona species tested . Additionally, it has been shown that swainsonine N -oxide was as effective as swainsonine in inhibiting α-mannosidase .…”
Section: Introductionmentioning
confidence: 99%